Autoimmune Hemolytic Anemia (AIHA) and Hypereosinophillia in Multiple Myeloma Patients in Saiful Anwar Hospital, Malang - RAHADIANTO; MAIMUN Z. ARTHAMIN (HANG TUAH MEDICAL JOURNAL, 2019)
ABSTRACT Multiple myeloma (MM) is a plasma cell dyscrasias characterized by five clinical signs namely anemia, monoclonal protein in serum and / or urine, bone radiology and abnormal bone pain, hypercalcemia and insufficiency and / or kidney failure. Autoimmune hemolytic anemia (AIHA) is a clinical condition where Ig G and or Ig M antibodies bind to the red blood cell surface antigen and destruction of red blood cells through the complement system and the reticuloendothelial system. Autoimmune hemolytic anemia (AIHA) is characterized by the production of antibodies directly against red blood cells. Autoimmune hemolytic anemia (AIHA) is characterized by the production of antibodies directly against red blood cells. AIHA is a disorder that does not occur frequently, with an estimated incidence of 1-3 cases per 100,000 per year. A patient of Multiple Myeloma with AIHA who is likely to occur because of a non-specific bond that occurs due to high levels of protein M or some abnormalities of the patient's red blood cells, also has an eosinophillia. Eosinophilia from peripheral blood is defined as absolute eosinophil count ≥ 0.5 x 109 / L. In general, eosinophilia is divided into familial type and acquired type. To find out the causes of eosifillia from these patients, it needs more in-depth observation and examination